Hubungan Skor Awal GCS Terhadap Lama Rawat Pasien P1, P2 dan P3 di IGD RSUD Dr. H. Moch. Ansari Saleh - Santia Andira Pradini; M. Sobirin Mohtar; Bagus Rahmat Santoso; santia, santiaandirapradini (Journal of Health, 2025)
Emergency care in a hospital started in ER and the most common problem on ER patients is consciousness decline. Consciousness could be measured with GCS score so the nurses could determine the right intervention. Nursery care quality in ER could be indicated by patient’s length of stay. The objective of this research is to analyze the correlation between initial GCS score to the length of stay of P1, P2, and P3 patients in ER RSUD Dr. H. Moch. Ansari Saleh. The results is ajority of respondents are adult (93,3%), male (53,3%), P2 triage or yellow triage (73,4%) and diagnosed as hypertensive patient (50%). Univariate analysis result showed that majority of respodents have full consciousness (73,3%) and have length of stay <ALOS 6 hours (56,6%). Rank spearman test result showed p value = 0,002 and correlation coefficient = 0,537 showed there is a strong correlation between GCS score to the length of stay of P1, P2, and P3 patients in ER RSUD Dr. H. Moch. Ansari Saleh. The conclusion is the higher patient’s initial GCS score, the length of stay will be shorter. Collaboration with laboratorium health worker and doctors are needed to cut patient’s length of stay in ER.